Lesson Study and Service Learning in Teacher Preparation - Soto, E.; Caparrós-Vida, Rosa María; Peña, N.; Servan-Núñez, María José (My University, 2018)
The aim of this paper is to share an teacher preparation experience that combines Lesson Study (LS) with a Service Learning methodology. This experience is interdisciplinary and includes three subjects from first-grade Childhood Education, carried out at University of Malaga since academic year 2014-2015. Within this framework, our students carry out Service Learning projects for schools in our area that are designed and developed following the LS methodology. Service Learning projects go through the following phases (Puig, J., Martín, & Batlle, 2008): 1) Preparation by the teachers involved in the project; 2) Implementation, i.e. developing the project with the students; 3) Evaluation. The implementation phase also has three sub-phases: preparation, implementation, and round-up. It is here that the LS is developed through the following phases (Soto & Pérez, 2015): 1. Define the problem; 2. Co-operatively design an experimental lesson and its observation process; 3. First experimental lesson; 4. Analyse and review the lesson; 5. Second experimental lesson; 6. Analysis and drafting of conclusions; 7. Presentation in extended context. We were able to gather evidence on how students teachers resolved different cognitive conflicts during the process. We saw how the LS process, with its phases and cooperative work, allows them to combine creativity and unique talents in a common project that acquires meaning and relevance thanks to Service Learning. This provides a framework that facilitates the construction of solid structures related to the meaning of the educational process, and which can be used to recalibrate what it means to be a Childhood School teacher: a creative, relevant, complex experience that requires recreating the knowledge and experience that students bring with them to the University about what it means to be a Childhood School teacher.
Keywords: Profesores - Formación profesional; Lesson Study; Aprendizaje Servicio; Formación inicial docente; Investigación-acción colaborativa; Desarrollo profesional docente